Proteostasis in Huntington’s disease: disease mechanisms and therapeutic opportunities - HARDING Rachel J; TONG Yu-feng (Acta Pharmacologica Sinica, 2018)
Abstract Many neurodegenerative diseases are characterized by impairment of protein quality control mechanisms in neuronal cells. Ineffective clearance of misfolded proteins by the proteasome, autophagy pathways and exocytosis leads to accumulation of toxic protein oligomers and aggregates in neurons. Toxic protein species affect various cellular functions resulting in the development of a spectrum of different neurodegenerative proteinopathies, including Huntington’s disease (HD). Playing an integral role in proteostasis, dysfunction of the ubiquitylation system in HD is progressive and multi-faceted with numerous biochemical pathways affected, in particular, the ubiquitin-proteasome system and autophagy routes for protein aggregate degradation. Unravelling the molecular mechanisms involved in HD pathogenesis of proteostasis provides new insight in disease progression in HD as well as possible therapeutic avenues. Recent developments of potential therapeutics are discussed in this review.